Russian language proficiency test for multilingual children = Sprachstandstest Russisch für mehrsprachige Kinder - Gagarina, Natalʹja Vladimirovna; Klassert, Annegret; Topaj, Nathalie (ZAS Papers in Linguistics, 2010)
The 'Russian language proficiency test for multilingual children' is a linguistically and psycholinguistically-grounded test for L1-Russian bilingual children of pre-school and elementary school age. It allows the evaluation of language proficiency in Russian for scientific, therapeutic, and pedagogical purposes. The test is based on preliminary norms: data of 167 German-Russian bilingual children between the ages of 3 years and 6 years 11 months were evaluated. Bilingual children's proficiency is examined in the following language domains: - productive and receptive lexicon for verbs and nouns - production of morphological marking on verbs (first and second-person singular present verbal inflection) and nouns (accusative and dative case singular) - comprehension of grammatical constructions on the sentence level The test should be administered by a competent – ideally native – speaker of Russian, and takes approximately 60 minutes to administer. In addition to the test itself, the 'Russian language proficiency test for multilingual children' contains a questionnaire for gathering detailed information on the input situation as well as the child's previous linguistic and extra-linguistic development. The questionnaire is written in English and Russian and is intended to be filled out by the parents.